Effects of Peer Support Arrangements Across Instructional Formats and Environments for Students With Severe Disabilities. (January 2018) - Schaefer, John M.; Cannella-Malone, Helen; Brock, Matthew E.
Peer support arrangements are an evidence-based practice for increasing interactions between students with severe disabilities and their peers in general education classrooms, but it is unclear how interactions vary across instructional formats or generalize outside the classroom. In this single-case design study, we tested the efficacy of peer support arrangements with three middle school students with severe disabilities, and focused on variability across instructional formats and generalization to the cafeteria and recess yard. We replicated previous findings of increased interactions and extended the literature by demonstrating positive effects across instructional formats with the largest gains during small group instruction and independent work time. We found no evidence of generalization; interactions only increased in nonclassroom settings after we directly targeted those settings. We recommend educators to implement peer support arrangements in general education classrooms, increase opportunities for small group instruction when appropriate, and purposefully target social interactions across settings.